Design of thermal cloak and concentrator with interconnected structure. (15th May 2022) - Sun, Tao; Wang, Xinhua; Yang, Xuyun; Meng, Tao; He, Renyang; Wang, Yuexin
Highlights: Proposing a new method for uniformly designing thermal cloak and concentrator with interconnected structure. The condition to realize undisturbed temperature distribution is strictly deduced. The thermal functionalities are demonstrated by theoretical derivation, FEM and experiments. Providing an efficient method for manipulating heat flux over a very wide range. Abstract: Heat flux manipulation based on thermal metamaterials under diffusive heat conduction has been extensively studied due to their extraordinary potential in energy utilization. However, the requirement of extreme material parameters or even infinite singularity may significantly limit their practical applications. In this work, we propose a new method for uniformly designing thermal cloak and concentrator with interconnected structure. The condition for realizing the undisturbed temperature distribution of the background medium in thermal cloak is strictly deduced. Through adjusting two geometric parameters of the interconnected structure, we analytically demonstrate that the thermal cloak and concentrator are realizable, where the heat flux can be shielded or concentrated in the target region. The desired thermal functionalities are confirmed both by the finite element simulations and heat transfer experiments. Furthermore, the results of interconnected structure are in excellent agreement with that of conventional thermal devices, and demonstrate that the interconnected structure provides an efficient method for manipulating heat flux over a very wide range (from cloaking to concentrating) despite having a simple composition and structural characteristics. The feasibility of interconnected structure can enhance the selection of bulk natural materials in addition to easy manufacturability for the heat flux manipulation, which might be extended to other disciplines, such as electromagnetics and acoustics.